Tingkat dan Faktor Risiko Kekebalan Protektif terhadap Rabies pada Anjing di Kota Makassar (RATE AND RISK FACTORS OF PROTECTIVE IMMUNITY AGAINST RABIES ON DOGS IN THE CITY OF MAKASSAR) - Utami, Sri; Sumiarto, Bambang (Jurnal Veteriner, 2012)
The rate and risk factors on protective immunity against rabies were conducted in Makassar city. Theaims of this study were to determine the level of immunity of dog and find out the association betweenmanagement factors and the level of maintenance of the dog immunity against rabies. Two hundred andforty-six serum samples were collected for measurement of dog immunity level with a method of enzymelinked immunosorbent assay (ELISA). Maintenance management data were gathered throughquestionnaires and direct observation. Analysis of data obtained by the level of immunity was donedescriptively. The significance association between the risk factors and the strength of immunity level wascalculated by using Chi square (X2) and odds ratios. The results showed only 12.2% of dogs had a protectiveantibody against rabies at > 0.5 IU/ml. Factors affecting the level of protective immunity against rabieswere the first vaccination at 1-6 months age (OR = 18.6), post-vaccination after 1-6 months (OR = 6.0), themaintenance location of dogs in urban areas (OR = 4.5), dog caring management in house (OR = 3.8), andowner income above Rp. 2.000.000/month (OR = 3.0). It is concluded that the low level of protective immunityagainst rabies and the dog bites reported each year indicates that Makassar, as endemic areal of rabies,is a threat to the outbreak of the disease in animals and humans to the surrounding areas.
Keywords: protective immunity rate, risk factors, rabies